2004
DOI: 10.1215/s1152851703000413
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 trial of BCNU plus irinotecan in adults with malignant glioma

Abstract: In preclinical studies, BCNU, or 1,3-bis(2-chloroethyl)-1-nitrosourea, plus CPT-11 (irinotecan) exhibits schedule-dependent, synergistic activity against malignant glioma (MG). We previously established the maximum tolerated dose of CPT-11 when administered for 4 consecutive weeks in combination with BCNU administered on the first day of each 6-week cycle. We now report a phase 2 trial of BCNU plus CPT-11 for patients with MG. In the current study, BCNU (100 mg/m2) was administered on day 1 of each 6-week cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…24 CPT-11 and topotecan have also shown some efficacy in the treatment of glioma. [25][26][27] However, low levels of efficacy when administered as a single agent and major toxicities such as colitis and interstitial pneumonia potentially limit their use for this purpose. 28,29 CKD-602 is a potent topoisomerase 1 inhibitor that does not have the poor water solubility and toxicity of its parent drug, camptothecin.…”
Section: Discussionmentioning
confidence: 99%
“…24 CPT-11 and topotecan have also shown some efficacy in the treatment of glioma. [25][26][27] However, low levels of efficacy when administered as a single agent and major toxicities such as colitis and interstitial pneumonia potentially limit their use for this purpose. 28,29 CKD-602 is a potent topoisomerase 1 inhibitor that does not have the poor water solubility and toxicity of its parent drug, camptothecin.…”
Section: Discussionmentioning
confidence: 99%
“…Using a combination of irinotecan and carmustine, Reardon et al 21 reported objective responses (one CR and four PRs) and a median TTP of 11.3 weeks in patients with recurrent malignant gliomas (including 28 with recurrent GBM), concluding that the combination was comparable in activity to single-agent irinotecan but with more frequent toxic effects. In contrast, another phase II trial of the same combination in patients with recurrent GBM on EIACs who had failed temozolomide was reported to have 9 PR and 21 SD, with a PFS-6 rate of 30.3% and a median TTP of 17 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…However, a phase II trial employing such a combination resulted in comparable results to that of CPT-11 alone and increased toxicity [68]. Similarly, ACNU, another nitrosourea given alone or in combination with teniposide or cytarabine in patients with GBM after TMZ failure resulted in limited activity and considerable toxicity [69].…”
Section: Other Irinotecan-based Combinationsmentioning
confidence: 99%